오이 유묘와 과실을 활용한 검은별무늬병에 대한 저항성 품종 검정 방법 - 심창기(Chang Ki Shim); 김민정(Min Jeong Kim); 박종호(Jong Ho Park); 한은정(Eun Jung Han); 박종원(Jong Won Park); 지형진(Hyeong Jin Jee); 김석철(Seok Cheol Kim); 김용기(Yong Ki Kim); 박소향(So Hyang Park); 홍성준(Sung Jun Hong) (Sigmulbyeong yeon'gu, 2016)
This study was conducted to elucidate the cultural and pathogenic characteristics of Cladosporium cucumerinum PT1 and resistance of 81 commercial cucumbers (Cucumis sativus). Cucumber leaves and fruits appeared as scab were collected from a plastic film house located in Pyeongtaek, Gyeonggi-province, Korea in late March, 2015. A casual fungus was isolated from the diseased fruits on potato dextrose agar and it was identified as C. cucumerinum PT1 based on the morphological characteristics. To find out the effect of wounding and fruit size on the development of cucumber scab, small (<10 cm long), medium (10 to 20 cm long), and large (>20 cm long, commercially mature fruit) size cucumber fruits were harvested, C. cucumerinum PT1 pathogens were inoculated with a single droplet of suspension ($1{×}10^5$ spores/ml) on wounded or unwounded cucumber fruits. Small fruits were completely damaged with showing severe water-soaking symptoms and fast pathogen growth regardless of wounded or unwounded. Meanwhile slight water-soaking symptoms on medium and large size fruits occurred and disease development into plant tissues was observed only on wounded fruits. Disease resistance of 81 commercial cucumber cultivars was evaluated on third-stage seedlings and small fruits by inoculating suspension ($1{×}10^5$ spores/ml) of C. cucumerinum PT1. As a result, mini and pickling cultivar groups were resistant, 'Cheoeumcheoreom' cultivar was symptomless and the other cultivars were resistant to medium resistant. On the other hand, most of cucumber cultivars belonging to the other groups were susceptible. Disease resistance of cucumber against cucumber scab was significantly different among cultivars and a few cucumber cultivars showed different disease resistant responses to two bioassay methods using seedlings and small fruits. Therefore, to screen scab resistance in cucumber, a test using both fruits and seedlings is advisable. We think that the selected resistant cultivars can be used to control cucumber scab effectively under the farmhouse condition. 본 연구는 검은별무늬병균의 배양적 및 병원학 특성을 구명하고, 81개 시판 오이 품종의 저항성 여부를 검정하기 위해 수행되었다. 시험균은 2015년 3월 말 경기도 평택에 위치한 시설 오이 재배농가에서 채취한 병든 과실로부터 분리하였고 PDA상에서 배양하면서 형태적인 특성에 근거하여 검은별무늬병균(C. cucumerinum PT1)으로 동정되었다. 상처 유무와 과실 크기가 검은별무늬병의 발생에 미치는 영향을 규명하기 위해 과일 크기를 유과(10 cm 미만), 중과(10-20 cm), 대과(20 cm 초과)로 구분하고 과실 크기별로 상처와 무상처 조건으로 오이 과실표면에 $1{×}10^5$ 포자/ml 농도의 병원균을 접종하였다. 작은 과실에서는 표면 상처 여부에 관계없이 심한 수침상의 병반과 빠른 병원균 생장을 보이면서 피해정도가 매우 컸던 반면, 중과와 대과에서는 상처 부위와 무상처 표면 모두에서 경미한 수침상의 병반이 나타났지만 식물체 안쪽 조직으로 병이 진전된 것은 상처 낸 과실에서 뿐이었다. 오이 유묘와 유과에 검은별무늬병균의 포자 현탁액을 접종하여 81개 시판 오이 품종의 병 저항성을 평가한 결과, 미니오이와 피클오이 품종군은 대부분 저항성이었다. 특히 '처음처럼' 품종은 아무런 병징이 나타나지 않았으며 나머지 품종들은 저항성-중도저항성으로 나타났다. 반면, 다른 품종군의 오이 품종은 대부분 감수성 품종으로 판명되었다. C. cucumerinum PT1에 대한 오이의 병 저항성은 품종 간 유의하게 차이를 보였으며 일부 품종에 있어서 유묘 검정과 유과 검정 간에 차이를 보였다. 따라서 검은별무늬병에 대한 저항성 품종을 선발하기 위해서 오이 유묘 검정과 유과 검정을 병행하여 사용할 필요가 있다고 생각한다. 이상의 결과를 토대로 선발된 저항성 품종을 농가에 적용한다면 오이 검은별무늬병 방제를 위한 실질적인 방법이 될 수 있을 것이라고 생각된다.